NCMP-05. LEFT BASAL GANGLIA/INTERNAL CAPSULE GLIOBLASTOMA WITH MEMORY LOSS FROM CONTRALATERAL RADIATION INDUCED VASCULOPATHIES. (12th November 2021) - Higgins, Shannon; Lassman, Andrew; Lennihan, Laura; Willey, Joshua; Wang, Tony; Sisti, Michael; Shapiro, Peter; Kim, Esther; Koshy, Amily
Abstract: INTRODUCTION: Radiation induced cerebral vasculopathy encompasses a complex and broad range of effects such as ischemia, hemorrhage, vascular malformation, capillary telangiectasias, and large vessel stenosis caused by pathological reorganization of tissue after radiation exposure. Necrosis and inflammation induce damage and demyelinating changes to other vessels over the corresponding areas that may occur months to years after brain irradiation. Here we report an unusual case of hemorrhagic basal ganglia/internal capsule glioblastoma followed by contralateral basal ganglia/internal capsule acute infarct with resulting acute transient global amnesia followed by chronic memory impairment. CASE REPORT: A 58-year old man was diagnosed with a hemorrhagic left basal ganglia/internal capsule mass after presenting with severe headaches, agitation, and vomiting. Glioblastoma (IDH wild type by sequencing, MGMT unmethylated) was identified on resection. He underwent radiotherapy and concurrent and adjuvant (12 cycles) temozolomide. Serial surveillance brain MRI scans demonstrated multiple incidental vascular abnormalities including subacute right basal ganglia/internal capsule ischemic infarct, right temporal cavernoma, and right temporal intra-parenchymal hemorrhage approximately 1, 2, and 3 years after diagnosis, respectively. Approximately 4 years after diagnosis, he presented with transient global amnesia and imaging demonstrated right basal ganglia/internal capsule ischemic stroke. DISCUSSION: Bilateral basal ganglia/internal capsule damage from stroke has been reported as causing memory impairment (Tatemichi TK et al, Neurology 1992;42:1966-79; PMID 1407580). Here we report memory impairment from unilateral basal ganglia/internal capsule tumor and contralateral infarct following brain radiotherapy as another mechanism of neurocognitive injury. Our case highlights the significance of continuing to surveil for these findings as new neurologic symptoms may mimic tumor progression.